2015
DOI: 10.3892/ol.2015.2852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological factors associated with Ki-67 expression in breast cancer patients

Abstract: The aim of the present study was to identify the optimal Ki-67 cut-off value in breast cancer (BC) patients, and investigate the association of Ki-67 expression levels with other prognostic factors. Firstly, a retrospective search was performed to identify patients with stage I–III BC (n=462). A range of Ki-67 index values were then assigned to five groups (<10, 10–14, 15–19, 20–24 and ≥25%). The correlation between the Ki-67 index and other prognostic factors [age, tumor type, histological and nuclear grade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
13
18
0
Order By: Relevance
“…39,40 Ki-67 is a nuclear protein that is commonly used for the detection and quantification of proliferating cells. 28 In agreement with the observations by others, 35,50,51 it was found that Ki-67 positively connected with Her-2 overexpression in this study, suggesting that Her-2 overexpression might upregulate the expression of Ki-67.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…39,40 Ki-67 is a nuclear protein that is commonly used for the detection and quantification of proliferating cells. 28 In agreement with the observations by others, 35,50,51 it was found that Ki-67 positively connected with Her-2 overexpression in this study, suggesting that Her-2 overexpression might upregulate the expression of Ki-67.…”
Section: Discussionsupporting
confidence: 81%
“…12 In agreement with the observation by Kobayashi et al, 61 our finding that p53 positive is connected with the progression of carcinoma to a higher histological grade and Her-2 overexpression in breast cancer patients suggests that p53 positive could be used as a prognostic biomarker for breast cancer 56,[62][63][64] in addition to being used as a diagnostic biomarker. 38 Our findings that Ki-67 positive is connected with the progression of carcinoma to a higher histological grade as well as Her-2 overexpression in breast cancer patients are consistent with the previous observations 5,35,50,61 and increase the reliability of this emerging biomarker 38 as a predictor of breast cancer prognosis outcomes. Our observation that both PR positive and ER positive are connected with a slower histological progress and are negatively connected with Her-2 overexpression in breast cancer supports that PR positive and ER positive are good biomarkers for predicting better prognosis and response to endocrine therapy than patients that lacked these receptors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Distinct breast cancer molecular subtypes are well associated with specific morphological characteristics and various clinical outcomes [3][4][5]. Previous studies reported that ER status was negatively correlated with Ki-67, suggesting that the high-proliferating breast tumors were observed in patients with ER-negative subtype [46,47]. Depletion of 5hmC has been identified depending on cell proliferation in numerous types of human cancer via passive demethylation [16][17][18][19].…”
Section: Discussionmentioning
confidence: 97%
“…The optimal cut-off value of the Ki-67-labeling index has been controversial, although there have been a number of reports on it [5] [6] [7] [8]. At the 2015 St. Gallen Consensus Conference, there was no optimal cut point of the Ki-67-labeling index.…”
Section: Introductionmentioning
confidence: 99%